The year we fell apart - Martin, Emily, 1987- (Simon Pulse, 2017)
A year ago Harper made the biggest mistake of her life by destroying her relationship with her best friend and first love Declan, so now that he is home from boarding school for the summer, Harper has three months to fix the year of miscommunications, secrets, and lies or finally let go altogether.